Multicast routing in internetworks and extended LANs. - Deering, S. E.
Multicasting is used within local-area networks to make distributed applications more robust and more efficient. The growing need to distribute applications across multiple, interconnected networks, and the increasing availability of high-performance, high-capacity switching nodes and networks, lead us to consider providing LAN-style multicasting across an internetwork. In this paper, we propose extensions to two common internetwork routing algorithms?distance-vector routing and link-state routing?to support low-delay datagram multicasting. We also suggest modifications to the single-spanning-tree routing algorithm, commonly used by link-layer bridges, to reduce the costs of multicasting in large extended LANs. Finally, we show how different link-layer and network-layer multicast routing algorithms can be combined hierarchically to support multicasting across large, heterogeneous internetworks.
Keywords: Theory of computation; Analysis of algorithms and problem complexity; Nonnumerical algorithms and problems; Routing and layout; Computer systems organization; Computer communication networks; Network architecture and design; Distributed networks; Packet switching networks; Ethernet; Algorithms; Design